Cr:forsterite laser frequency comb stabil[a]zation and development of portable frequency references inside a hollow optical fiber - Thapa, Rajesh (Kansas State University, 2008)
We have made significant accomplishments in the development of portable frequency standard inside hollow optical fibers. Such standards will improve portable optical frequency references available to the telecommunications industry. Our approach relies on the development of a stabilized Cr:forsterite laser to generate the frequency comb in the near-IR region. This laser is self referenced and locked to a CW laser which in turn is stabilized to a sub-Doppler feature of a molecular transition. The molecular transition is realized using a hollow core fiber filled with acetylene gas. We finally measured the absolute frequency of these molecular transitions to characterize the references. In this thesis, the major ideas, techniques and experimental results for the development and absolute frequency measurement of the portable frequency references are presented. A prism-based Cr:forsterite frequency comb is stabilized. We have effectively used the prism modulation along with power modulation inside the cavity in order to actively stabilize the frequency comb. We have also studied the carrier-envelope-offset frequency (f0) dynamics of the laser and its effect on laser stabilization. A reduction of f0 linewidth from [similar to]2 MHz to [similar to]20 kHz has also been observed. Both our in-loop and out-of-loop measurements of the comb stability showed that the comb is stable within a part in 10^11 at 1-s gate time and is currently limited by our reference signal. In order to develop this portable frequency standard, saturated absorption spectroscopy is performed on the acetylene v1+v3 band near 1532 nm inside different kinds of hollow optical fibers. The observed linewidths are a factor 2 narrower in the 20 um fiber as compared to 10 um fiber, and vary from 20-40 MHz depending on pressure and power. The 70 um kagome fiber shows a further reduction in linewidth to less than 10 MHz. In order to seal the gas inside the hollow optical fiber, we have also developed a technique of splicing the hollow fiber to solid fiber in a standard commercial arc splicer, rather than the more expensive filament splicer, and achieved comparable splice loss. We locked a CW laser to the saturated absorption feature using a Frequency Modulation technique and then compared to an optical frequency comb. The stabilized frequency comb, providing a dense grid of reference frequencies in near-infrared region is used to characterize and measure the absolute frequency reference based on these hollow optical fibers.
Keywords: frequency comb metrology; Cr:forsterite laser; saturation spectroscopy; fiber splicing; Ultrafast optics; portable frequency reference; Physics, Optics (0752)